Character education values: is learning process in elementary school implement it? - Aci Pratiwi; Darmiany Darmiany; Heri Setiawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aimed to determine the implementation of character education values at SDN 19 Rabangodu Utara, Bima City. The type of research used is mixed methods research with an exploratory design. This type of research combines qualitative and quantitative research. In this study, the researchers developed a questionnaire instrument and an observation sheet. Data collection techniques used in this study are observation, interviews (interviews), questionnaires (questionnaires), and documentation. The data analysis technique used descriptive data analysis techniques according to Miles and Huberman for qualitative data and descriptive statistical analysis for quantitative data. Based on the results of data analysis, the results of the study indicate that (1) The process of implementing character education values carried out at SDN 19 Rabangodu Utara, Bima City through self-development activities (routine activities, spontaneous activities, exemplary and conditioning) and integration in thematic learning ( Syllabus and lesson plans and the learning process). (2) The behavior of students in applying character values (religious, honest, diligent, disciplined, and caring/responsible) is in the sufficient category as many as 52 people (61.17%). The rest in the good category as many as 18 people (21.18%), and in the less category as many as 15 people (17.65%). (3) Obstacles faced by schools in the process of implementing character education values include the lack of attention from some parents to students, the online habits of students who like to play gadgets and watch TV, and lack of room infrastructure at SDN 19 Rabangodu Utara, Bima City.